Integration of Microanatomy, Neuronavigation, Dynamic Neurophysiologic Monitoring, and Intraoperative Multimodality Imaging for the Safe Removal of an Insular Glioma: 2-Dimensional Operative Video. Issue 1 (3rd May 2021) - Wu, Kyle; Bi, Wenya Linda; Essayed, Walid Ibn; Patel, Viharkumar; Kadri, Paulo; Al-Mefty, Ossama
Abstract: Insular gliomas are located amongst myriad critical neurovascular structures, including lenticulostriate vessels, long insular perforators, putamen, internal capsule, frontal and temporal opercula, and key fasciculi. 1-6 Each of these critical structures engenders key function of the brain, which must be preserved. Although anatomic knowledge remains the cornerstone of insular glioma surgery, novel tools have been developed to aid the surgeon in identifying and preserving these essential structures. Modern surgery of the insular glioma calls for seamless integration of these techniques to maximize the safety and totality of insular glioma resection, which has been shown to improve length of survival and seizure control, while reducing risk of tumor transformation. 7-10 Neuronavigation can be used to help plan the craniotomy to achieve adequate exposure and assist during tumor resection. Brain "shift" can be corrected by re-registration following intraoperative magnetic resonance imaging (MRI). Interval ultrasound imaging reflects real-time progressive tumor resection. Dynamic neurophysiologic monitoring using thresholding techniques guides the surgeon as he resects tumor at its depth and posterior pole—close to the internal capsule. Intraoperative magnetic resonance imaging depicts residual infiltrative tumor that may require additional resection. The patient is a 33-yr-old woman with progressive growth of a right insular tumor and has consented to surgery, photography, and video recording. Figure at 1:57, © Ossama Al-Mefty, used with permission.